Mulu Borneo stalagmite SC02 U/Th dating and oxygen and carbon stable isotopes, 19.5-10.7 ky BP - Frances Buckingham; Stacy A Carolin; Jud Partin; Jess F Adkins; Kim M Cobb; Christopher Day (PANGAEA, 2022)
Here are presented Mulu, Borneo (4°6 extquotesingleN, 114°53 extquotesingleE) Secret Cave stalagmite SC02 d18O and d13C values over Termination 1, published in Buckingham et al. (2022). U-Th ages were calculated using the initial detrital 230Th/232Th value of 111 ± 41 ppm, which was previously calculated for SC02 based on two isochrons measured in separate stalagmites from Secret Cave in Mulu (Carolin et al., 2013). A Matlab Monte Carlo script was used to calculated the absolute age and age errors associated with each U-Th sample using the 234U and 230Th half lives presented in Cheng et al. (2013). The Poisson-process deposition model feature in OxCal(v4.4) was used to interpolate between the eighteen U/Th ages to produce an age model (Bronk Ramsey, 2008; Bronk Ramsey and Lee, 2013). This study reports a d18O and d13C record for the portion of SC02 104.1 to 182.4 mm distance from top of stalagmite. The d18O record spans the full deglaciation, and reveals for the first time distinct d18O variations connected with the Bølling-Allerød onset and the Younger Dryas event.